The generation mechanism of cold eddies and the related heat flux exchanges in the upper ocean during two sequential tropical cyclones - Shen, Zheyue; Zhang, Shuwen (Frontiers in Marine Science, 2022)
The impacts of two sequential tropical cyclones (TCs), Kyarr and Maha, [from October 24 to November 06, 2019, over the Arabian Sea (AS)] on upper ocean environments were investigated using multiple satellite observations, Argo float profiles and numerical model outputs. During Kyarr and Maha, three distinct cold patches were observed at the sea surface with a maximum sea surface cooling of approximately 5°C. To obtain a realistic TC strength, WRF model simulation was used to reproduce Kyarr and Maha. The simulation results showed that the WRF model indicated high simulation accuracy with respect to the SST decrease in the AS under the influence of Kyarr and Maha’s wind stress curls. Moreover, the locations of these cold eddies were highly correlated with three obvious negative SSHAs, and through the use of eddy detection algorithms, three mesoscale cold cyclonic eddies were identified along the TC paths. The radii of the cold eddies were e1~69 km, e2~50 km, and e3~41 km. With a focus on the thermodynamic responses of the three cold eddy fields to Kyarr and Maha, the centres of these cold eddies were detected, exhibiting relatively shallow mixed-layer depths (MLDs) and low mixed-layer temperatures (MLTs). The depth integrated heat (DIH) content was also calculated to explore the heat exchange occurring in different layers in the upper 200 m of the centre of each eddy. The results showed that DIH in each eddy centre under each TC varied by one order of magnitude, accounting for between 127.3 MJ m-2 and 1220.0 MJ m-2 of heat loss. This study suggests that the effect of intense wind stress curls, long forcing time of strong wind (speed >17 m/s) and positive relative vorticity injected into the sea surface in three certain areas are the three main influencing factors of the generation mechanism of cold eddies. TC-induced vertical mixing and upwelling (strengthened by unstable structures inside the cold eddies) cause substantial redistribution of the DIH, and related heat exchange at different layers occurs in the eddy fields.